System of Subjective Deixis Means in B.L. Pasternak’s Early Prose - S. A. Soloveva (Научный диалог)
The means and methods of subjective deixis, participating in the organization of the forms of subjective-author's narration is analyzed in the article. Their role in the formation of text interpretation strategies is determined. The relevance of the problem is associated with the peculiarities of the research material — the texts of the early prose of B. L. Pasternak, the montage of which is manifested in the alternation of points of view, the nonlinearity of the structure. This complicates the process of the reader's interpretation. The use of methods of continuous sampling, descriptive, contextual and interpretive types of analysis made it possible to reveal the specifics of the linguistic means of subjective deixis, the system of deictic relations. The analysis showed that the absence of marked transitions between exegetical (third-person narration) and diegetic (first-person narration) narrators leads to the fact that the deictic functional is simultaneously assigned to a complex of linguistic means used within the framework of one utterance or text fragment. These are personal pronouns and discursive elements that activate the reader’s attention. Inconsistency in the use of forms of subjective-author’s narration leads to the formation of hybrid models. It reflects the process of the author’s search, an attempt to establish deictic parity (synchronicity of perception) between the author, character, reader and “observer”, forms new relations in the author-reader system.